Decision support in the absence of necessary information and models by means of OLAP-systems: organisational and managerial perspectives. (24th February 2004) - Anisimov, Alexander
Formal methodologies of decision support and formal presentation of decision making processes commonly imply development (or selection) of appropriate algorithms and models (preferably mathematical) and their subsequent practical usage. But rapid changes of economical, market and technological conditions often make it impossible to develop comprehensive decision making models and corresponding procedures thereby enforcing decision making under uncertainty. As a rule, in such situations managers and analysts may rely mostly on information about facts that took place in the past. That is why flexible access to such data is crucial for practical management. Our approach sets up a paradigm for the integration of On-Line Analytical Processing systems into managerial processes with respect to support urgent decision making in the situation when development of comprehensive models is impossible. We also discuss corresponding organisational framework aimed to ensure practical realisation of this paradigm.